Estudo quimico de Baccharis dracunculifolia DC. e sua correlação com a própolis de uma microrregião dos Campos Gerais do Paraná - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2009)
This study aimed to chemically analyze extracts of propolis samples and leaves of plant species of the Baccharis genus in the region of Ponta Grossa - PR, to classify the regional propolis compared to the green propolis (PG12). Baccharis dracunculifolia, the source of green propolis, may present metabolic changes related to environmental factors. To compare with published data, the essential oils obtained by hydrodistillation from the leaves of female (0.81%) and male (0.85%) specimens of B. dracunculifolia harvested in the dry season were analyzed by GC-MS. The two samples showed a low monoterpenes/sesquiterpenes ratio (0.85/96.88% ♀; 2.35/ 95.25% ♂). The monoterpenes b-pinene, limonene and terpinen-4-ol were identified. The main sesquiterpenes hydrocarbons are b-caryophyllene (♀ 7.88%; ♂ 8.88%), b-humulene (♀ 4.61%; ♂ 2.18%), germacrene D (♀ 5.53%; ♂ 4.04%) trans-b- guaiene (♀ 7.98%; ♂ 6.06%) and cadinene (♀ 7.34%; ♂ 5.48%). The oxygenated sesquiterpenes (E)-nerolidol (♀ 24.69%; ♂ 17.16%) and spathulenol (♀ 14.62%; ♂ 21.39%) were found as the major constituents. The high yield, the low monoterpenes / sesquiterpenes ratio and the high proportions of oxygenated sesquiterpenes are the main characteristics of the essential oil of B. dracunculifolia from this region. The leaves of three species of Baccharis (B. dracunculifolia, B. semiserrata and B. uncinella) were extracted using a Soxhlet apparatus with the sequence of solvents chloroform, ethyl acetate and methanol, and the extracts were analyzed by TLC, UV and HPLC. Free phenolic acids were identified: caffeic acid (Bd ♀ and Bd ♂), p-coumaric acid (Bd ♀), ferulic acid (Bd ♀, ♂ Bd, Bu and Bs) and the flavonoid rutin (Bd ♀, Bd ♂, Bu). Thus, it is demonstrated for the first time, the co-occurrence of polar phenolic substances in these three plant species. The ethanol extracts obtained from 13 samples of propolis were analyzed by TLC-HR and UV-VIS, allowing the classification of the regional propolis in three groups. The most characteristic sample of each type (ADI, WS- 3, RS-2) was chosen for analysis by HPLC in comparison with green propolis PG12. Fresh sprouts of male and female specimens of B. dracunculifolia were extracted by rinsing with methanol and the extracts were analyzed by HPLC. All extracts of propolis and B. dracunculifolia showed artepillin C ensuring that this plant is the source of regional propolis. The caffeic acid, ferulic acid and p-coumaric acid were identified in the four samples of propolis. Apigenin is present only in the regional propolis samples, between 2.4% and 3.9%, while crisin was identified only in the PG12, but as a main component (18.1%). An unidentified flavonoid (lma x 365 nm, 42,96 min) is the main substance present in the three samples of regional propolis and also the extract obtained by the rinsing of the plant sprouts. All the ethanol extracts of regional propolis showed excellent levels of antioxidant activity when tested against the radical DPPH, several of them getting to be more effective than the PG12. A comparative analysis of antioxidant power and chemical composition of the samples indicates that the unidentified flavonoid is responsible for the strong antioxidant activity of ADI and WS-2 compared to RS-2 and PG12.
Keywords: Baccharis dracunculifolia; óleo essencial; própolis regionais; atividade antioxidante; CLAE; Baccharis dracunculifolia; essential oil; regional propolis; antioxidant activity; GC-MS; HPLC; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA